2009
DOI: 10.1002/lary.20562
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency surgery of the soft palate in the treatment of mild obstructive sleep apnea is not effective as a single‐stage procedure: A randomized single‐blinded placebo‐controlled trial

Abstract: RF surgery of SP is not recommended as a single-stage approach in mild OSAS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 13 publications
4
32
2
1
Order By: Relevance
“…However, patients in the group without concurrent tonsillectomy (group C) performed significantly poorer regarding AHI as an objective outcome measure than did those who had tonsillectomy, suggesting that patients benefit far less from RAUP than from tonsillectomy. This finding is corroborated by a placebo-controlled trial which showed that radiofrequency surgery of the soft palate was ineffective for treatment of mild-to-moderate OSA [13]. …”
Section: Discussionsupporting
confidence: 64%
“…However, patients in the group without concurrent tonsillectomy (group C) performed significantly poorer regarding AHI as an objective outcome measure than did those who had tonsillectomy, suggesting that patients benefit far less from RAUP than from tonsillectomy. This finding is corroborated by a placebo-controlled trial which showed that radiofrequency surgery of the soft palate was ineffective for treatment of mild-to-moderate OSA [13]. …”
Section: Discussionsupporting
confidence: 64%
“…5) The presence of inter-study variability between sham and not sham studies was not ascribable to mean or median age of patients but possibly to other factors. 6) The absence of psychological and psychiatric profile that is relevant for studies were the placebo effect have to be evaluated represents a very important confounding factor [10], [22], [24], [25], [26], [27], [28], [29], [30], [31], [32], [33], [34], [35], [36], [37], [38], [39], [40], [41], [42], [43], [44], [45], [46], [47], [48], [49], [50], [51], [52], [53], [54], [55], [56], [57], [58], [59], [60], [61], [62], [63], [64], [65], [66], [67], [68], [69], [70], [71], [72], [73], [78], [79]. 7) A percentage of 5% of participants lost to the follow-up has been extracted from 30 on the 52 studies examined (ref.).…”
Section: Resultsmentioning
confidence: 99%
“…However, there are inconsistent findings in daytime sleepiness or other sleep parameters. A more recent, placebo-controlled study has shown that a single step radiofrequency intervention at the soft palate is not effective for the treatment of OSA (table e20) [228].…”
Section: Overview Of the Evidencementioning
confidence: 99%